Nurse’s Therapeutic Alliance, Relationship Building, and Therapeutic Communication Strategies for The Symptom Schizophrenia Population - Prabawati, Chlara Yunita; Pratiwi, Mutia (Universitas Muhammadiyah Surabaya, 2021)
A severe mental disorder affects thought, feelings, and behaviour defined as Schizophrenia. The involve primary symptoms of Schizophrenia, are experiencing hallucinations, delusion, anhedonia, avolition, asociality, apathy, alogia, and attention disorder. The practice of the registered nurse-patient relationship might be used to examine the level of symptoms of patients with Schizophrenia. The purpose of this study is to examine the relationship between the Nurse’s Therapeutic Alliance, Relationship Building, and Therapeutic Communication with the symptoms of the patient with Schizophrenia. The design was a correlational study using a cross-sectional approach. This study was conducted at the inpatient department of a government mental hospital in Indonesia with participants sixty-three adult schizophrenic patients and twenty-five registered nurse nurses. The primary outcome measure used a questionnaire the Nurse - Client Relationship Phase (NCRP), Brief Psychiatric Rating Scale (BPRS) and the Brief Negative Symptoms Scale (BNSS). The result of this study shows that there is a significant positive correlation (p < .05) between the registered nurse-patient relationship involving three sub-domains with the negative symptoms of schizophrenic patients; a significant positive correlation (p < .001) was found between therapeutic communication strategies, relationship building with the negative symptom. However, a lower correlation was found between the registered nurse-patient relationship with the negative symptoms of schizophrenic patients. In addition, registered nurses are expected to improve their abilities and services, especially in terms of determining the strategy of communicating with patients.